Antibacterial and Antifungal Properties of Hedyosmum cuatrecazanum Occhioni Essential Oil: A Promising Natural Alternative Studied Using Neutrosophic SuperHyperSoft Sets - María Eugenia Lucena de Ustáriz; Francisco Javier Ustáriz-Fajardo; Adriana Monserrath Monge Moreno; Adriana Isabel Rodríguez Basantes; Lisbeth Josefina Reales Chacón; Rosa Elisa Cruz Tenempaguay; Verónica Paulina Cáceres Manzano; Nathaly Kassandra Moscoso Moreno (Neutrosophic Sets and Systems)
Antimicrobial resistance is a global public health issue that, exacerbated by inappropriate an tibiotic use, leads to reduced bactericidal effects, multidrug resistance, increased medical costs, pro longed hospital stays, and higher mortality rates. This study evaluates the antibacterial and antifungal activity of the essential oil of Hedyosmum cuatrecazanum Occhioni against various clinically relevant bac terial and fungal strains. The essential oil was extracted by hydrodistillation, yielding a 0.26% extract. Its components were characterized by gas chromatography coupled with mass spectrometry (GC-MS). The results demonstrate that the essential oil exhibits significant antibacterial activity, comparable to commercial antibiotics. Hedyosmum cuatrecazanum oil showed the highest antibacterial activity against S. aureus and antifungal activity, where C. albicans and C. tropicalis were the most susceptible. For the study, the effective relative values of the chemical components of the essential oil were modeled using Fuzzy_Extension SuperHyperSoft Sets theory, as well as their concentration. Specifically, we model in determinacy with the use of single-valued triangular neutrosophic numbers. This is because the per centages of each chemical that makes up the essential oil vary in a certain range from one plant to an other. This mathematical tool allows us to determine the percentages and concentrations in which the essential oils are most effective in treating bacteria and fungi.